Integrating business management processes. Volume 3, Harmonising quality, food safety and environmental processes - De Silva, Titus (New York, NY : Routledge, 2021)
Integrating Business Management Processes: Volume 3: Harmonising Quality, Food Safety and Environmental Processes (978-0-367-48547-4) Shelving Guide: Business & Management The backbone of any organisation is its management system. It must reflect the needs of the organisation and the requirements of its customers. Compliance with legal requirements and ethical environmental practices contributes towards the sustainability of the management system. Whatever the state of maturity of the management, this book, one of three, provides useful guidance to design, implement, maintain and improve its effectiveness and is intended to provide readers with practical "how to" methods for integrating quality, safety and environmental management processes. This volume sets out procedures and flowcharts to show how the integration of these processes can be achieved. Separated into management procedures, core procedures, support procedures and assurance procedures and complemented by practical examples, this book is an invaluable resource for complete systems development and integration. This book, along with its two companion volumes, is a practical guide for real managers, designed to help them manage their business more effectively and gain competitive advantage. Titus De Silva is a consultant in management skills development, pharmacy practice, quality management and food safety and an advisor to the newly established National Medicines Regulatory Authority (NMRA) in Sri Lanka.
MP 015 Production Planning -- MP 016 Looking After Our Customers -- MP 017 Management of Emergencies -- MP 018 Emergency Response Planning -- MP 019 Actions to Address Risks and Opportunities -- MP 020 Change Management -- MP 021 Control of Product and Service Changes -- Section II: Core Procedures -- CP 001 Approval of Suppliers -- CP 002 Offering Contracts -- CP 003 Purchasing Information -- CP 004 Purchasing -- CP 005 Purchasing Engineering Items -- CP 006 Purchasing Technology Resources -- CP 007 Inward Goods Receipt -- CP 008 Inward Goods Inspection -- CP 009 Issue of Inward Goods
"A Productivity Press book."
CP 010 Inspection and Test Status
OCLC-licensed vendor bibliographic record.
Keywords: Industrial management; Environmental management; BUSINESS & ECONOMICS / Leadership; BUSINESS & ECONOMICS / Management